Peran Organisasi Karang Taruna dalam Meningkatkan Sumber Daya Manusia - Iqbal Rasyid Endrian (Jurnal Bintang Manajemen, 2023)
This research was conducted because he wanted to find out more regarding "The Role of Youth Organizations in Improving Human Resources" in accordance with the main issues raised, namely the role of youth organizations in improving human resources in Kepuh Kemiri Village, Tulangan District, Sidoarjo Regency. Which aims to explain the role and efforts of Karang Taruna in increasing human resources in Kepuh Kemiri Village. The research method used is qualitative. The subjects of this study were the youth committee and local residents. By using data collection techniques, namely through interviews and observation. The results of this study indicate that there are several activities, roles and efforts of youth organizations that have not been maximized in the development of human resources. Members of youth organizations with student status also help in human resource development. The conclusion that can be drawn from this research is that the role played by youth board members with student status is to improve discipline, provide motivation for all youth youth members. Some of the supporting factors include: Adequate human resources owned by administrators with student status, Responsibility and cooperation from all parties, There is support from the community.